Nakba Memoricide: Genocide Studies and the Zionist/Israeli Genocide of Palestine. Issue 1 (May 2014) - Rashed, Haifa; Short, Damien; Docker, John
<x xml:space="preserve">Abstract</x> This essay furthers the debate on the Palestinian case as it relates to Genocide Studies, questioning the lack of substantive discussion of this case to date in traditional Genocide Studies fora. It reemphasises the importance of the settler-colonial dimension to Zionist settlement in Palestine, which, it argues, has so far not been explored sufficiently. The paper suggests that the 'Nakba' of 1948, which was based on appropriation of the land of Palestine without its people, comprising massacres, physical destruction of villages, appropriation of land, property and culture, can be seen as an ongoing process and not merely a historical event.